A review on environmental DNA (eDNA) metabarcoding markers for wildlife monitoring research - N., Othman; H., Haris; Z., Fatin; M. F., Najmuddin; N. H., Sariyati; B. M., Md-Zain; M. A. B., Fatin (2020)
Environmental DNA or eDNA utilizes traceable genetic materials in the environment for monitoring the presence of organisms in a given area and it is now gaining popularity as an alternative for traditional monitoring methods. Thus, the selection of genetic markers is crucial for identification of species in wildlife monitoring. This paper aims to review several DNA markers which are appropriate and reliable for detection of organisms from the environmental samples. We performed systematic literature search from SCOPUS database to review all molecular markers of eDNA. This study focuses on the importance of markers selection which can be utilized by next-generation sequencing (NGS) for biodiversity monitoring. Cytochrome C oxidase Subunit I (COI) are noted as the most widely used marker in metabarcoding research for detection of targeted species.